Imbalances of the Caribbean Basin countries with respect to NAFTA : the garment industry - Gitli, Eduardo (2000)
Examines the underlying concern over the possible effects of NAFTA and the Mexican devaluation on the export performance of the economies of the region; in order to quantify the impact of these two factors on the relative competitiveness of the Caribbean Basin garment industry in relation to Mexico.